Sex‐specific seasonal variation in puma and snow leopard home range utilization. Issue 8 (20th August 2018) - Johansson, Örjan; Koehler, Gary; Rauset, Geir Rune; Samelius, Gustaf; Andrén, Henrik; Mishra, Charudutt; Lhagvasuren, Purevjav; McCarthy, Tom; Low, Matthew
Abstract: Territory size is often larger for males than for females in species without biparental care. For large solitary carnivores, this is explained by males encompassing a set of female territories to monopolize their reproduction during mating (area maximization). However, males are expected to behave more like females outside of breeding, with their area utilization being dependent on the range required to secure food resources (area minimization). To examine how male and female solitary carnivores adjust their spatial organization during the year as key resources (mates and prey) change, we radio‐collared 17 pumas ( Puma concolor ; nine males and eight females) and 14 snow leopards ( Panthera uncia ; seven males and seven females) and estimated home range size and overlap on two temporal scales (annual vs. monthly). Contrary to expectation, we found no evidence that males monopolized females (the mean territory overlap between females and the focal male during the mating season was 0.28 and 0.64 in pumas and snow leopards, respectively). Although male–male overlap of annual home ranges was comparatively high (snow leopards [0.21] vs. pumas [0.11]), monthly home range overlaps were small (snow leopards [0.02] vs. pumas [0.08]) suggesting strong territoriality. In pumas, both males and females reduced their monthly home ranges in winter, and at the same time, prey distribution was clumped and mating activity increased. In snow leopards, females showed little variation in seasonal home range size, following the seasonal stability in their primary prey. However, male snow leopards reduced their monthly home range utilization in the mating season. In line with other studies, our results suggest that female seasonal home range variation is largely explained by changes in food resource distribution. However, contrary to expectations, male territories did not generally encompass those of females, and males reduced their home ranges during mating. Our results show that male and female territorial boundaries tend to intersect in these species, and hint at the operation of female choice and male mate guarding within these mating systems.